2022
DOI: 10.1017/dmp.2022.141
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital Emergency Service Challenges in the Face of the COVID-19 Pandemic in Iran

Abstract: Background: With the outbreak of Coronavirus Disease 2019 (COVID-19), the workload of the Iran’s health care system along with Pre-hospital Emergency Service (PHES) increased significantly so that Iranian fledgling emergency system had never experienced such a crisis. With regard to the importance of the function of PHES as the front line staff of Iran’s health system and its role in controlling the recent epidemic crisis, this study was conducted to identify the challenges of PHES function in the face of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The challenge of lack of equipment has been mentioned in many Iranian studies (10,11,21,22). One of the most important reasons that caused Iran to deal with such a stubborn problem more severely than other countries is the sanctions against Iran, which has imposed a serious challenge on the process of supplying health and medical appliances to centers and personnel (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge of lack of equipment has been mentioned in many Iranian studies (10,11,21,22). One of the most important reasons that caused Iran to deal with such a stubborn problem more severely than other countries is the sanctions against Iran, which has imposed a serious challenge on the process of supplying health and medical appliances to centers and personnel (34).…”
Section: Discussionmentioning
confidence: 99%
“…Weakness in personnel training, including method of working with personal protective equipment and safety, lack of maneuvers, etc., were some of the challenges raised in the present study. The lack of adequate training of personnel to deal with epidemic conditions in many countries shocked managers by the widespread prevalence of the disease and caused them not be prepared to deal with the related conditions and challenges (21). This challenge has also been reported for hospital personnel of Sweden, Iran, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has posed unprecedented challenges for prehospital medical staff globally ( WHO, 2020b ; Shakibnia et al, 2021 ; Heidari et al, 2023 ), including those in Iran ( Heidari et al, 2023 ). Reluctance to care for highly infectious patients has led to adverse events during prehospital transport, even for short distances, potentially resulting in life-threatening situations ( Baru et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…While several international studies have examined the experiences of prehospital medical staff during the COVID-19 pandemic ( Piotrowski et al, 2021 ; Nyashanu et al, 2022 ; Tune et al, 2022 ), limited research exists on the specific challenges faced by Iranian prehospital medical staff during the COVID-19 pandemic, particularly during the Delta wave ( Hadian et al, 2022 ; Heidari et al, 2023 ). Hadian et al highlighted the adverse impact of inadequate equipment and job overload on mental health and emergency care quality ( Hadian et al, 2022 ), while Heidari et al identified individual and systemic challenges requiring organizational planning and policy attention ( Heidari et al, 2023 ). However, there is still a noticeable gap and limitations in understanding the lived experiences of Iranian prehospital medical staff within the unique context of their services, especially during the Delta wave.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency room (ER) physicians, nurses and nursing assistants face extreme situations in their daily clinical practice that require a quick response; hence, they work under constant pressure. In addition, these professionals deal with patients and their suffering, which entails a significant emotional and psychosocial demand that implies an overload of work, stress and negative consequences for health (Azevedo et al, 2017; Heidari et al, 2022; Munnangi et al, 2018; Pacheco, 2009).…”
Section: Introductionmentioning
confidence: 99%